PU.1 expression in T follicular helper cells limits CD40L-dependent germinal center B cell development - Awe, Olufolakemi (J Immunol, 2015)
PU.1 is an ETS family transcription factor important for the development of multiple hematopoietic cell lineages. Previous work demonstrated a critical role for PU.1 in promoting Th9 development, and in limiting Th2 cytokine production. Whether PU.1 has functions in other T helper lineages is not clear. In this report we examined the effects of ectopic expression of PU.1 in CD4+T cells and observed decreased expression of genes involved with the function of T follicular helper (Tfh) cells, including Il21 and Tnfsf5 (encoding CD40L). T cells from conditional mutant mice that lack expression of PU.1 in T cells (Sfpi1(lck−/−)) demonstrated increased production of CD40L and IL-21 in vitro. Following adjuvant-dependent or adjuvant-independent immunization, we observed that Sfpi1(lck−/−) mice had increased numbers of Tfh cells, increased germinal center B cells, and increased antibody production in vivo. This correlated with increased expression of IL-21 and CD40L in Tfh cells from Sfpi1(lck−/−) mice, compared to control mice. Finally, although blockade of IL-21 did not affect germinal center B cells in Sfpi1(lck−/−) mice, anti-CD40L treatment of immunized Sfpi1(lck−/−) mice decreased germinal center B cell numbers and antigen-specific immunoglobulin concentrations. Together, these data indicate an inhibitory role of PU.1 in the function of T follicular helper cells, germinal centers, and Tfh-dependent humoral immunity.